0137 Bold fMRI Correlates Of Intermittent Sympathetic Vasoconstriction During Light Sleep. (27th April 2018) - Ozbay, P S; Chang, C; Picchioni, D; Mandelkow, H; Moehlman, T; Chappel-Farley, M; van Gelderen, P; de Zwart, J A; Duyn, J H
Abstract: Introduction: Variations in sympathetic and parasympathetic activity during sleep can lead to fluctuations in heart rate and vascular tone, potentially confounding fMRI measurements of brain activity that rely on hemodynamic signals. To investigate this, photo-plethysmography (PPG) based measurements of peripheral vasoconstriction were correlated with fMRI signals acquired during an overnight sleep study. Methods: BOLD fMRI data was obtained at 3T with gradient-echo-EPI (flip-angle=90 0, repeatition-time=3s, echo-time=36ms, voxel-size=2.5x2.5x2mm 3, matrix-size=96x70x50, acceleration-factor=2). EEG and ECG were acquired concurrently with the fMRI with a 64-channel recorder (61 EEG scalp, 2 electro-oculography, and 1 ECG electrodes), synchronized to the MRI system-clock. Heart rate (HR), vascular tone inferred from PPG signal amplitude (AMP), and respiratory volume (RV) were derived from the PPG and chest belt signals. Initial inspection of all data (n=16) showed, primarily during N1/N2 sleep, striking variations in AMP, consisting of intermittently occurring 10-15s drops accompanied by a biphasic change in HR. Based on this a subset of data was selected (~20% of the scans) that had a high incidence of AMP drops and fMRI without motion artifacts. Results: AMP drops had a strong correlate in the fMRI signal in both grey-matter (GM) and white-matter (WM). The covariation of fMRI signal and PPG-AMP often exceeded that with the more conventional physiological measures of HR and RV. Voxel-vise correlations between PPG-AMP and fMRI signals showed a striking negative correlation in central WM and around medullary-veins at 0-lag, turning positive after about 3-6s. In GM, maximum positive correlation was observed at around 6s time-lags. Conclusion: Intermittent AMP drops are interpreted as systemic vasoconstrictive events, possibly relating to correlations between EEG measures of arousal and AMP drops, as previously observed during sleep (Ackner et al., 1957). The fMRI effects suggest that this vasoconstriction also involves the central-nervous-system vasculature. The lag-dependent characteristic of the WM signal can be explained by a temporal mismatch between blood-volume and blood-oxygenation effects originating from vascular transit delays. A similar mechanism may explain previous findings of WM fMRI signals during both task- and resting-state fMRI. Support (If Any): Intramural Research Program of the NINDS.